Separation of cognitive impairments in attention-deficit/hyperactivity disorder into 2 familial factors - Kuntsi, Jonna; Wood, Alexis C.; Johnson, Katherine A.; Andreou, Penelope; Arias-Vasquez, Alejandro; Buitelaar, Jan K.; Rommelse, Nanda N. J.; Sergeant, Joseph A.; Sonuga-Barke, Edmund J.; Uebel, Henrik; van der Meere, Jaap J.; Banaschewski, Tobias; et al. (Archives of general psychiatry, 2010)
Attention-deficit/hyperactivity disorder (ADHD) is associated with widespread cognitive impairments, but it is not known whether the apparent multiple impairments share etiological roots or separate etiological pathways exist. A better understanding of the etiological pathways is important for the development of targeted interventions and for identification of suitable intermediate phenotypes for molecular genetic investigations.To determine, by using a multivariate familial factor analysis approach, whether 1 or more familial factors underlie the slow and variable reaction times, impaired response inhibition, and choice impulsivity associated with ADHD.An ADHD and control sibling-pair design.Belgium, Germany, Ireland, Israel, Spain, Switzerland, and the United Kingdom.A total of 1265 participants, aged 6 to 18 years: 464 probands with ADHD and 456 of their siblings (524 with combined-subtype ADHD), and 345 control participants.Performance on a 4-choice reaction time task, a go/no-go inhibition task, and a choice-delay task.The final model consisted of 2 familial factors. The larger factor, reflecting 85% of the familial variance of ADHD, captured 98% to 100% of the familial influences on mean reaction time and reaction time variability. The second, smaller factor, reflecting 13% of the familial variance of ADHD, captured 62% to 82% of the familial influences on commission and omission errors on the go/no-go task. Choice impulsivity was excluded in the final model because of poor fit.The findings suggest the existence of 2 familial pathways to cognitive impairments in ADHD and indicate promising cognitive targets for future molecular genetic investigations. The familial distinction between the 2 cognitive impairments is consistent with recent theoretical models—a developmental model and an arousal-attention model—of 2 separable underlying processes in ADHD. Future research that tests the familial model within a developmental framework may inform developmentally sensitive interventions.Arch Gen Psychiatry. 2010;67(11):1159-1167-->
Gesehen am 08.03.2023